Harnessing the Antioxidant, Anti-Inflammatory, and Neuroprotective Potential of Fagonia arabica’s Biogenic Gold Nanoparticles in SK-N-SH Neuroblastoma Cells - Gurmeet Kaur Surindar Singh, (Asian Journal of Pharmaceutics (AJP), 2025)
Aims: The biogenic synthesis and characterisation of gold nanoparticles (AuNPs) made from the aqueous extract of Fagonia arabica plant were investigated in this work, as well as their antioxidant, anti-inflammatory, and neuroprotective potential. Materials and Methods: The dried plant material underwent successive solvent extraction. The resulting crude extracts were subjected to standard phytochemical analyses, and the aqueous extract was further subjected to quantitative analysis for total phenols and flavonoids. The synthesized AuNPs were characterized using Fourier Transform Infrared Spectroscopy, ultraviolet-visible, X-ray diffraction, energy-dispersive X-ray (EDX), prostate-specific antigen, scanning electron microscopy, and zeta potential analysis. The in vitro anti-inflammatory activity was assessed using cyclooxygenase-2 (COX-2) inhibition and protein denaturation assays. Whereas the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) assay was employed to determine the antioxidant activity. Cytotoxicity was tested on the L929 cell line, whereas the in vitro neuroprotection assessment was done on the SK-N-SH cell line. The data were provided as mean ± standard error of the mean, and a statistical analysis was performed by a two-tailed unpaired t-test. Results: The phytochemical analysis of the extracts identified flavonoids, alkaloids, and phenols. The aqueous extract’s total phenol and flavonoid content was found to be 2450.35 µg gallic acid equivalent/g and 1980.29 µg quercetin equivalent (QE)/g, respectively. The AuNPs were successfully characterized using various techniques, confirming their stability and optimal characteristics. The AuNPs showed crystalline nature, an average size of 111.4 nm, and a zeta potential value of −2.1 mV. The EDX analysis confirmed the presence of gold with an atomic weight of 27.5%. In vitro assays showed potent anti-inflammatory activity by protein denaturation (IC50 118.65 µg/ mL), COX-2 inhibition (IC50 109.67 µg/mL); antioxidant activity confirmed by DPPH scavenging assay (IC50 115.01 µg/ mL). Furthermore, the AuNPs exhibited minimal toxicity on normal L929 cell lines (IC50 246.57 µg/mL), indicating good biocompatibility.